Edukasi Pencegahan Kanker Serviks pada Wanita Usia Subur (WUS) di Posyandu Lavenda Kelurahan Kenali Besar Kota Jambi - Sirly Patriani; Selpyani Sinulingga (Jurnal Abdimas Kesehatan (JAK), 2022)
Cervical cancer is a disease that has a broad psychosocial impact, especially for patients and their families. In Indonesia, there are about 50 new cases of cervical cancer per 100,000 population per year. cervical cancer is a malignant tumor disease in the cervical area as a result of uncontrolled tissue growth and damage the surrounding normal tissue. Posyandu Lavenda is one of the active posyandu and has represented Jambi Province in the Posyandu competition to the National level. The Lavenda Posyandu was also chosen as a place tso be used as a Pendopo as a place for meetings between RTs. As a form of activity, the Lavenda posyandu was once a place for a free IVA (Visual Acetate Inspection) test held by Kenali Besar Health Center officers. IVA test is one way to detect early for the prevention of cervical cancer. This community service is carried out by providing education through counseling to WUS women about cervical cancer prevention. held from October to January 2022 at the Lavenda Posyandu, Kenali Besar Village. The purpose of this service activity is to provide education by providing health education/counseling on cervical cancer prevention, with the hope of increasing WUS knowledge and awareness in preventing cervical cancer. The results obtained after community service was carried out were an increase in WUS knowledge about cervical cancer prevention at the Lavenda Posyandu, Recognized Besar Sub-district, Jambi City. The implementation of community service activities carried out by conducting education (counseling) using leaflets was able to increase WUS knowledge about cervical cancer prevention.